STUDY ON LAND SURFACE TEMPERATURE CHARACTERISTICS OF HOT MUD ERUPTION IN EAST JAVA, INDONESIA - Luhur Bayuaji; Hiroshi Watanabe; Hideyuki Tonooka; Josaphat Tetuko Sri Sumantyo; Hiroaki Kuze (National Institute of Aeronautics and Space of Indonesia (LAPAN), 2009)
hot mud has erupted in sidoarjo, east Java, Indonesia since 29 May 2006. It started as natural gas exploration project and punctured a geological structure at a depth of 2,8 km, releasing unprecedented volume of hot mud volcano (5x104 mcubix per day). By November 2006, it was estimated that hot mud had spread over (2,89 plus minus 0,10) x 106 m, swamping several villages with more than 10.000 people evacuated. In this research, by employing the advantage of spatial perspective of remote sensing imagery, the extent of hot mud spreading area and temperature distributions are derived from satellite images of the advanced Spaceborn Thermal Emission and Reflection Radiometer (ASTER) sensor onboard the Terra satellite. The mud spreading are was calculated using three visible or near infrared channels having a resolution of 15 m. Temperature distributions were calculated using the temperature or emissivity separation (TES) method on five thermal infraredchannels with a resolution of 90 m. The standard and water vapor scaling (WVS) methods were applied in the atmospheric correction process prior to the TES process. The result showed that the mud continued spreading during five months after the eruption. After 3-5 months from the eruption, the estimated temperature was about 30-69 degree of celcius in the mud spreading area. Also, estimations of the volume and weight of the hot mud were made on the basis of the visible of level 3 A product of ASTER and ground survey data. Keyword ASTER TIR, ASTER VNIR, Hot mud volcano, Temperature emissivity separation, Water vapor scaling method.